2020
DOI: 10.3390/w12030662
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Bank-Filtration Occurrence in the Province of Quebec (Canada) with a GIS Approach

Abstract: Due to the abundance of surface water in the province of Quebec, Canada, it is suspected that many groundwater wells are pumping a mixture of groundwater and surface water via induced bank filtration (IBF). The regulatory framework in Quebec provides comprehensive guidelines for the development and monitoring of surface water and groundwater drinking water production systems. However, the regulations do not specifically address hybrid groundwater-surface water production systems such as IBF sites. More knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Lake A water sampling was performed in the northern part of the lake for logistical reasons and due to ease of accessibility. As horizontal homogeneity has been previously demonstrated by Pazouki et al (2016), the water samples were deemed representative of the whole waterbody.…”
Section: Water Sampling and Analytical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lake A water sampling was performed in the northern part of the lake for logistical reasons and due to ease of accessibility. As horizontal homogeneity has been previously demonstrated by Pazouki et al (2016), the water samples were deemed representative of the whole waterbody.…”
Section: Water Sampling and Analytical Techniquesmentioning
confidence: 99%
“…In comparison, the neighbouring lake (i.e. lake B) does not undergo yearly recurrent flooding and was shown to be more mineralized with a Na-Cl water type, likely originating from the road salt contamination of regional groundwater (Pazouki et al, 2016). Biehler et al (2020) similarly reported hydrological controls on the geochemistry of a shallow aquifer in an hyporheic zone, where the river stage influenced the mixing ratio between river water and the deeper aquifer.…”
Section: Resilience Of Lakes To Groundwater Pollutionmentioning
confidence: 99%
“…In the same area of south east Canada that contains many streams and lakes and a huge number of municipal water supply wells, Patenaude et al [6] posed the question "which of these are in fact induced river bank filtration wells that may require greater protection from potential surface water pollution?" They used a GIS with multi-criteria decision analysis (MCDA) to categorise the likelihood of wells inducing infiltration from surface water.…”
Section: Water Quality Improvementmentioning
confidence: 99%
“…BF systems in hilly terrains were also reported to be vulnerable to contamination during flood events (Sandhu et al, 2013). In the province of Quebec (Canada), it is not rare to observe pathogen indicators (such as total coliforms) in municipal pumping wells during springtime freshets, which is perhaps linked to the fact that bank filtration is likely performed unintentionally due to the large density of lakes and rivers, and the close proximity of municipal wells to those waterbodies (Patenaude et al, 2020).…”
Section: Introductionmentioning
confidence: 99%